RELEVANSI NILAI INFORMASI AKUNTANSI, INTELLECTUAL CAPITAL, CORPORATE GOVERNANCE, PERSISTENSI LABA DAN ASIMETRI INFORMASI - Claudya Hutauruk; Dwi Fitri Puspa (Fakultas Ekonomi dan Bisnis Universitas Bung Hatta, 2023)
Value relevance of accounting information is the ability of accounting information to explain or describe company values ​​that will assist information users in understanding and making financial decisions. This study aims to empirically examine the effect of intellectual capital, corporate governance (as measured by managerial ownership, institutional ownership, independent commissioners and audit committees), earnings persistence and information asymmetry on value relevance (as measured by stock prices) in basic materials companies listed on the Indonesia Stock Exchange in 2017 – 2021. Using the purposive sampling method, a sample of 36 companies was obtained. The type of data used in this research is secondary data obtained from www.idx.co.id. Hypothesis testing was carried out using multiple linear regression analysis using eviews 12 software. The results showed that book value per share, earnings per share, intellectual capital, and managerial ownership had a negative and significant effect on stock prices. Institutional ownership has a positive and significant effect on stock prices. Independent board of commissioners, audit committee, earnings persistence and information asymmetry have no effect on stock prices.